2014
DOI: 10.1016/j.tvjl.2013.10.024
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a spot-on formulation containing polyunsaturated fatty acids and essential oils on dogs with atopic dermatitis

Abstract: Recent studies have shown that immunological aberrations and epidermal barrier defects could be important in the pathogenesis of canine atopic dermatitis (CAD) and that oral polyunsaturated fatty acids (PUFAs) might influence the epidermal barrier. The aim of this study was to evaluate the effects of a spot-on formulation containing PUFAs and essential oils on pruritus and lesions caused by CAD. Forty-eight privately owned dogs of different breeds, ages and genders diagnosed with atopic dermatitis were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 27 publications
0
31
1
2
Order By: Relevance
“…In the present study, there were no significant differences between the treatment and placebo groups for any of the evaluated clinical and skin barrier parameters. This is in contrast to other studies which demonstrated improvements in CADESI scores and/or pruritus after the use of topical fatty acids . However, most of these studies used different products with different frequencies of application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, there were no significant differences between the treatment and placebo groups for any of the evaluated clinical and skin barrier parameters. This is in contrast to other studies which demonstrated improvements in CADESI scores and/or pruritus after the use of topical fatty acids . However, most of these studies used different products with different frequencies of application.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the influence of topical and oral fatty acids on the skin barrier in dogs are few in number and have either been performed in purposefully sensitized dogs within a research environment, or in clinical subjects using nonstandardized protocols. Nevertheless, topical and oral fatty acids reportedly restored the skin barrier, improved clinical signs and decreased medication requirements in dogs with AD …”
Section: Introductionmentioning
confidence: 99%
“…Dogs were allowed to be on concurrent medications for treatment of atopic dermatitis. However, dosing of these medications could not have changed for a minimum amount of time prior to inclusion of the study, as follows: 12 months for allergen‐specific immunotherapy, 4 months for oral glucocorticoids, 4 months for oral ciclosporin (+/− ketoconazole), 3 months for oral fatty acids, 1 month for oral antihistamines and 1 month for topical therapy . Doses were required to stay consistent throughout the study.…”
Section: Methodsmentioning
confidence: 99%
“…Klinische Untersuchungen zeigten, dass eine Behandlung von an atopischer Dermatitis und an nicht generalisierter Dermatitis erkrankten Hunden mit kommerziell erhältlichen Formulierungen, die unter anderem ätherische Öle enthielten, zu einer Besserung der Symptomatik führten [8][9][10]. Ebenfalls zeigte sich bei bakteriell bedingter oberflächlicher Pyodermie durch eine zusätzlich zur antibiotischen Therapie durchgeführte topische Behandlung mit einem Manukaöl enthaltenden Präparat eine schnellere klinische Besserung, die unter anderem durch die antibakterielle Wirkung des Manukaöls bedingt sein könnte [11].…”
Section: Schlüsselwörterunclassified